Heart rate turbulence in type 2 diabetes mellitus with chronic kidney disease. - Huimin Zhu; You-Fan Peng; Huiping Gu; Xingjing Liu (PLoS ONE, 2025)
Objective Heart rate turbulence (HRT), a test quantified by turbulence onset (TO) and turbulence slope (TS), has been used to assess cardiac autonomic neuropathy (CAN). CAN is a complication of chronic kidney disease (CKD) in patients with type 2 diabetes mellitus (T2DM). Thus, this study aimed to assess the association between HRT parameters and CKD in T2DM patients. Methods This retrospective study included 322 patients with T2DM, grouping them into those with and those without CKD; the data collected from the patients with T2DM were analysed. T2DM was diagnosed according to American Diabetes Association criteria. CKD diagnoses were confirmed according to KDIGO Clinical Practice Guidelines. Results For HRT parameters, T2DM patients with CKD exhibited a significantly higher turbulence onset (TO) (-0.25 [-1.02, 0.23] vs -0.64 [-1.93 0.10], p = 0.034) and lower turbulence slope (TS) (2.49 [1.27, 4.00] vs 6.20 [2.55, 8.80], p < 0.001) than those without CKD. TO was significantly negatively correlated with estimated glomerular filtration rate (eGFR) (r = -0.184, P = 0.001), whereas TS was significantly positively correlated with eGFR in patients with T2DM (r = 0.203, P < 0.001). Multivariable logistic regression analysis revealed that higher TS, but not for TO, was independently associated with CKD in patients with T2DM(OR=0.885, 95%CI:0.8400.932, P < 0.001). Conclusion Higher TS, an HRT parameter reflecting heart rate deceleration following ventricular premature beat, was independently associated with CKD in T2DM patients. This study suggests that CKD may change heart rate deceleration following ventricular premature beat in T2DM patients, which may be helpful in improving CAN assessment by HRT in patients with CKD.